Parametric design of efficient high-rise buildings: Development of a design and analysis tool for the early design stages - Sarreshtedari, Samira (My University, 2024)
High-rise buildings have become increasingly popular during the past few decades. They have a large potential in providing more floor area for the same building footprint. However, high-rise buildings also require more material in their structural systems to withstand the wind loads that they are subjected to due to their height. High-rise buildings are therefore generally regarded as an unsustainable building type, making it even more important to analyze and optimize their structural systems in early design stages to minimize their environmental impact. This thesis investigates how a parametric design and analysis tool can be developed and utilized in the early design stages of a high-rise building. By parametrizing a FE-model of the core, the tool computes data on the structural performance and climate impact of several designs. This allows for evaluation of an optimal structural design in regard to low climate impact while fulfilling the structural requirements. The tool development consists of an intuitive tool for the very early design stages in Rhinoceros 3D and Grasshopper, as well as an in-depth analysis tool in ETABS with scripting in Excel and VBA. The aim with the Rhino/Grasshopper tool is to obtain preliminary dimensions and understand the structural behavior of the core. The tool in ETABS computes data on the structural performance and CO2e of several designs, allowing to make informed design decisions based on a set of evaluation criteria. The outcome of this thesis indicates that there is a significant possibility of reducing the material usage and climate impact of the core of a high-rise building. The most important factor is to reduce the amount of concrete in the core, which is preferably achieved by increasing the dimensions of the core and decreasing the core wall thicknesses. Lastly, the thesis concludes that the utilization of parametric tools in the construction industry is a valuable asset in decreasing the climate impact of high-rise buildings.
Keywords: High-rise buildings; Tall buildings; Optimization; CO2e; Parametric design; Grasshopper; Octopus; Python; ETABS; VBA; Tableau